Letter (copy) : Senor Jose Rodriguez Vega - Citrine, Walter, 1887-1983
013-0006-001 International. WMC/WJB/DT/400. Private & Confidential 11th December, 1942. Dr. J. Negrin, 15, Grosvenor Square, W.1. Dear Dr. Negrin, SENOR JOSE RODRIGUEZ VEGA I have received your letter of December 10th and was interested and pleased to know that our colleage Senor Rodriguez Vega is in Lisbon. I quite agree it would be most useful to see him here in London and have therefore asked that steps be taken so that the necessary facilities may be granted to enable him to make the journey to this country. Yours sincerely, General Secretary. 292/946/13/6